Intra-Abdominal injuries in isolated thoracolomber transverse process fractures (Annals of Medical Research, 2022)
Aim: We aimed to investigate the frequency of intra-abdominal injury in posttraumatic isolated transverse process fractures (iTPF) and the factors affecting the injury, especially the effect of the size of the fracture on the injury.Materials and Methods: Patients' age, gender, trauma type determined by Computed Tomography (CT), fracture localization, separation distance of the fracture from the vertebral body, neurological status, and non-vertebral organ injury, if any, were evaluated retrospectively.Results: Intra-abdominal injury was detected in 16 of 70 patients with iTPF included in the study. The most common cause of iTPF was falls. Those with multiple TPF had a higher rate of intra-abdominal injury. Liver injury was the most common type of intra-abdominal injury. The separation distance of iTPFs from the vertebral body was mean 5.81±1.9 mm in patients with intra-abdominal injury and 3.90±1.69 mm in patients without intra-abdominal injury, and the separation distance was statistically significantly higher in patients with intra-abdominal injury (p
Keywords: Vertebra; ısolated transverse process fracture; intra-abdominal injury